Preparation and characterization of anticorrosive and antibacterial coatable nanocomposite based on zinc phosphate modified by Hydroxy Apatite/alginate: Investigation of electrochemical impedance spectroscopy (EIS) - Arezoo Mohammadkhani; Faezeh Mohammadkhani; Mirabdullah Seyed Sadjadi; Nazanin Farhadyar; Mohammad Jaafar Soltanian Fard; Ehsan kianfar; Mehdi Zakani (Case Studies in Chemical and Environmental Engineering, 2024)
In This study, three new surface-modified antibacterial and anticorrosive nanocomposites (zinc Phosphate- Polyvinyl Pyrrolidone, Zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite and Zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite/Alginate) were synthesized in low-temperature by facile and efficient method. We crosslink Alg with Zn2+ and Ca2+ to make it insoluble and enhancing of their physical and biological properties (zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite/Alginate). Nanocrystals were characterized by (XRD), (FT-IR), (EDX), (SEM) and (TEM). the TEM image showed that the core shell nanocrystal had good dispersion with a particle size of 8–36, 12–38 and 10–45 nm, respectively. Antibacterial rate of the Zinc Phosphate- Polyvinyl Pyrrolidone, Zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite and Zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite/Alginate NPs reached near 100%. To analyze the EIS results obtained from the equivalent circuits, parameters such as Rct, CPEdl, Rf, n, CPEf, and Rt were extracted. Nyquist diagrams demonstrated that the Zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite sample had better protection than the Zinc Phosphate- Polyvinyl Pyrrolidone and Zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite/Alginate sample, at all immersion time. The phase angle of the Zinc Phosphate- Polyvinyl Pyrrolidone (-θ 11°/96 h) was a greater value compared with the Zinc Phosphate- Alginate sample (-θ 10°/96 h) and Zinc Phosphate- Polyvinyl Pyrrolidone/Hydroxy Apatite/Alginate (-θ 4.2°/96 h), indicating a transition from capacitive to inductive behavior with longer immersion times.